Handbook of Single-Molecule Biophysics - Hinterdorfer, Peter; van Oijen, Antoine (Springer New York : Imprint: Springer, 2009)
The last decade has seen the development of a number of novel biophysical methods that allow the manipulation and study of individual biomolecules. The ability to monitor biological processes at this fundamental level of sensitivity has given rise to an improved understanding of the underlying molecular mechanisms. Through the removal of ensemble averaging, distributions and fluctuations of molecular properties can be characterized, transient intermediates identified, and catalytic mechanisms elucidated. By applying forces on biomolecules while monitoring their activity, important information can be obtained on how proteins couple function to structure. The Handbook of Single-Molecule Biophysics provides an introduction to these techniques and presents an extensive discussion of the new biological insights obtained from them. Coverage includes: Experimental techniques to monitor and manipulate individual biomolecules The use of single-molecule techniques in super-resolution and functional imaging Single-molecule studies of physical properties of biomolecules Single-molecule enzymology and biochemistry Single molecules in the membrane Single-molecule techniques in living cells Integration of single-molecule biophysics and nanoscience.